Crown ether-based structures for sensitive electrochemical detection. (August 2015) - Simionca, Ioana-Maria; Arvinte, Adina; Pinteala, Mariana
N -(2-Hydroxypropyl)methacrylamide-co- N -acryloxysuccinimide with 2-aminomethyl-18-crown-6 (p(HPMA-NAS-18C6)) graft copolymer deposited on the gold (Au) electrode is able to bind heavy metal cations from aqueous solutions. The binding of the lead(II) cations (Pb 2+ ) is monitored by quartz crystal microbalance, cyclic voltammetry, and anodic stripping voltammetry. Electrochemical studies have demonstrated that the presence of p(HPMA-NAS-18C8) on the Au electrode surface resulted in the shift of Pb oxidation wave to less negative potentials, accompanied by the increase of the oxidation peak magnitude. The p(HPMA-NAS-18C6)-modified electrode could sensitively detect Pb 2+ cations in a range from 10 ppb to 4.39 ppm with a low detection limit of 0.17 ppb.